A kinetic study of autohydrogenotrophic denitrification at the optimum pH and sodium bicarbonate dose - Ghafari, S.; Hasan, M.; Aroua, M.K. (Bioresource Technology, 2010)
In this study the kinetics of autohydrogenotrophic denitrification was studied under optimum solution pH and bicarbonate concentration. The optimal pH and bicarbonate concentration were firstly obtained using a design of experiment (DOE) methodology. For this purpose a total of 11 experiments were carried out. Sodium bicarbonate concentrations ranging of 20-2000 mg/L and pH values from 6.5 to 8.5 were used in the optimization runs. It was found that the pH has a more pronounced effect on the denitrification process as compared to the bicarbonate dose. The developed quadratic model predicted the optimum conditions at pH 8 and 1100 mg NaHCO 3/L. Using these optimal conditions, the kinetics of denitrification for nitrate and nitrite degradation were investigated in separate experiments. Both processes were found to follow a zero order kinetic model. The ultimate specific degradation rates for nitrate and nitrite remediation were 29.60 mg NO - 3-N/g MLVSS/L and 34.85 mg NO - 3-N/g ]MLVSS/L respectively, when hydrogen was supplied every 0.5 h.